Pengabdian Kepada Masyarakat pada Usaha Keripik Pisang Nangka Desa Limau Manis Kecamatan Tanjung Morawa Kabupaten Deli Serdang - Ninny Siregar; Kamaluddin Lubis; Nuril Mahda (Universitas Medan Area, 2020)
The business carried out by Ms. Maimunah is a home industry located on Jl. Hasan Tua Dusun III B Limau Manis Village, Tanjung Morawa District, Deli Serdang Regency. This business has tremendous potential because the production of banana chips derived from jackfruit bananas is made through a simple processing process. With the help of banana slicing machines, the production of jackfruit banana chips has increased, from 50-60 kg / day with a working time of 8 hours / day to 150-200 kg / day. This can be done by increasing productivity in the production management system and marketing management system.